2021
DOI: 10.3390/atmos12121635
|View full text |Cite
|
Sign up to set email alerts
|

A Model-Based Climatology of Low-Level Jets in the Weddell Sea Region of the Antarctic

Abstract: Low-level jets (LLJs) are climatological features in polar regions. It is well known that katabatic winds over the slopes of the Antarctic ice sheet are associated with strong LLJs. Barrier winds occurring, e.g., along the Antarctic Peninsula may also show LLJ structures. A few observational studies show that LLJs occur over sea ice regions. We present a model-based climatology of the wind field, of low-level inversions and of LLJs in the Weddell Sea region of the Antarctic for the period 2002–2016. The sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…The average frequency of occurrence of PLLJ over Antarctica and Greenland is very high, about 59%; with some locations having values above 90%. This is broadly consistent with previous studies (e.g., Heinemann & Zentek, 2021; Tuononen et al., 2015). The development of PLLJs is similar to inertial oscillations that one expected due to near‐surface inversion formed by little irradiance in polar nights causing low surface temperatures throughout the day for several months (Figure 6c).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The average frequency of occurrence of PLLJ over Antarctica and Greenland is very high, about 59%; with some locations having values above 90%. This is broadly consistent with previous studies (e.g., Heinemann & Zentek, 2021; Tuononen et al., 2015). The development of PLLJs is similar to inertial oscillations that one expected due to near‐surface inversion formed by little irradiance in polar nights causing low surface temperatures throughout the day for several months (Figure 6c).…”
Section: Resultssupporting
confidence: 93%
“…LLJs are known to occur in different regions around the world that favor the development of different types. Common locations for LLJ occurrence are coastal upwelling regions (Lima et al., 2022), hot deserts (Fiedler et al., 2013; Heinold et al., 2013) and continental polar regions (Heinemann & Zentek, 2021; Tuononen et al., 2015). LLJs in hot desert areas are usually NLLJs, although a fraction of the LLJs are connected to convective cold pools (Heinold et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of the radiosonde data with the simulations for the lowest 600 m for the complete month of July 2018 showed that only a few LLJs were detected in the radiosonde data (Supplementary Material Figure S8), while the simulations showed frequent LLJs, which were associated with channeled flow in most cases (Supplementary Material Figure S9). The time resolution, as well as the problems of radiosonde wind measurements in the lowest 100 m, made it difficult to detect LLJs in operational radiosoundings [10,29,30]. It should be noted that measurements at Cape Baranova (synoptic data and radiosondes) were not used for the ERA5 reanalyses, which were used as initial and boundary conditions for the CCLM simulations.…”
Section: Wind Distributionsmentioning
confidence: 99%
“…The case studies already showed good examples of LLJs associated with channeling. The analysis of LLJs follows the method used in [30]. The lowest wind maximum was searched for below 1000 m, then the next minimum above the maximum was searched for below 1500 m, but limited by a search radius of 1.5 times the height of the maximum.…”
Section: Climatology Of Lljsmentioning
confidence: 99%